Online recruiment practises in mid size family companies - De Alwis, A.Chamaru (Univerzita Pardubice, 2010)
This paper presents current development of the Internet as recruitment in family companies in Sri Lankan context. The methodology of the study was conducted on family companies in different industries by collecting data through questionnaires and follow up interviews. Results indicate that usage level of internet for recruitment process is comparatively lower. However it indicates that there will be an increase usage of internet for recruitment in the future with the expected advancements in the IT infrastructure availability and affordability.
Keywords: e-recruitment; human resource management; internet